The potential of autonomous emergency braking for motorcycles and mopeds.
According to the European Road Safety Observatory (ERSO), the risk of a fatality while riding a motorcycle or moped per kilometre travelled is 12 times higher than for driving a car. An EU initiative has explored the potential use of a road vehicle safety system for 'Powered two wheelers' (PTWs).